Analisis Kesulitan Belajar dan Strategi Penanganan dalam Konteks Pendidikan Agama Islam: Perspektif Psikologi dan Nilai-Nilai Qur’an (Indo-MathEdu Intellectuals Journal, 2025)
Learning difficulties are a complex challenge in the world of education that can hinder students' academic achievements. This research aims to analyze the causes, characteristics, and strategies for addressing learning difficulties, particularly in the context of Islamic Education (PAI) learning. Using a descriptive qualitative approach based on literature study, this study identifies two main factors causing learning difficulties, namely internal factors (cognitive, motivational, and psychological) and external factors (family, school, and social environment). Data is obtained through a literature review of scientific books, journal articles, previous research findings, and relevant Islamic sources. Data analysis techniques are conducted through qualitative content analysis. The research results indicate that learning difficulties impact low academic achievement and the emergence of maladaptive learning behaviors. Effective handling strategies include adaptive pedagogical interventions through the stages of identification, diagnosis, prognosis, and targeted assistance. This study emphasizes the importance of revitalizing digital-based learning methods and integrating Qur'anic values, such as patience, gratitude, and noble character, as reflected in Surah Al-Insyirah and Luqman. The synergy between teachers, parents, and the educational environment is key in creating an inclusive and meaningful learning atmosphere